The Effectiveness of Self-Expandable Metallic Stent Insertion in Treating Right-Sided Colonic Obstruction: A Comparison between SEMS and Decompression Tube Placement and an Investigation of the Safety and Difficulties of SEMS Insertion in Right Colons - Rintaro Moroi; Katsuya Endo; Ryo Ichikawa; Hiroshi Nagai; Hirohiko Shinkai; Tomoya Kimura; Fumitake Ishiyama; Kei Yaguchi; Shoichi Kayaba; Tooru Shimosegawa (Gastroenterology Research and Practice)
Objectives. Self-expandable metallic stent (SEMS) is widely used to treat malignant colonic obstruction. However, most reports about SEMS insertion have concentrated on the left colon. This study aimed to (1) investigate the effectiveness of SEMS insertion compared with conventional decompression tube for right-sided colonic obstruction and (2) compare the safety and technical success of SEMS insertion between left- and right-sided colonic obstructions. Methods. The data from thirty-seven patients who underwent SEMS or conventional decompression tube placement for malignant colonic obstruction in our hospital were analyzed retrospectively. Technical and clinical success, complications, and technical difficulties were analyzed. We compared the results between SEMS insertion and decompression tube placement in right colons and the outcomes of SEMS insertion between right- and left-sided colonic obstructions. Results. For right colons, the clinical success rate of SEMS insertion (100%) was significantly higher than that of decompression tube placement (55.9%). Concerning SEMS insertion, the technical difficulty and safety of SEMS insertion were similar between right- and left-sided colonic obstructions. Conclusion. SEMS insertion for right-sided colon is significantly more effective than conventional decompression tube placement, and this procedure was safer and less technically challenging than expected. SEMS insertion should be considered for treating right-sided malignant colonic obstruction.